Obama's challenge : America's economic crisis and the power of a transformative presidency - Kuttner, Robert (Carlton North, Vic. : Scribe, 2008)
A great president or a failed one -- How transformative presidents lead -- Audacity versus undertow -- Repairing a damaged economy -- A work in progress.
First published in the United States by Chelsea Green, 2008.
Includes bibliographical references (p. 204-209) and index.
Keywords: Obama, Barack; Financial crises -- United States; Global Financial Crisis, 2008-2009.; Political leadership -- United States; United States -- Economic policy